IMLPEMENTASI KETAHANAN WILAYAH PERBATASAN DAN PULAU-PULAU TERLUAR DALAM RANGKA MENEGAKKAN KEDAULATAN NEGARA - Siswanto, Dwi Joko; Gatot Subagya; Agustin Nurhandayani; Herdin Yudha Puspita; Agus marwanto; Muhammad Fachry Rizky; Mardhendi Beriasta Ginting (PPM Sdirjianbang Akademi Militer, 2024)
Development in border areas and outer islands is very significant, considering that the border area, has considerable natural resource potential, is a very strategic area for the defence of state security and can be used as a security fortress at the front door of the territory of the Republic of Indonesia, but in reality the development of border areas. especially the Tanimbar Islands Regency, which can be implemented by the government and the Army in increasing regional resilience so that border areas and outer islands in the 1507 / Saumlaki Kodim area. can become the ‘front porch’ of the Republic of Indonesia. This paper uses a qualitative descriptive method, with a literature approach. To analyse existing data in building a strategy concept using the SWOT Analysis Method. Strategies that can be carried out to build the resilience of border areas include the preparation of RT / RW that reach the border areas of the country, improving the quality of human resources, building facilities and infrastructure, bringing the title of Army units closer to the border area and empowering border security posts to assist local governments in improving community welfare.